Combination of grading and new biological factors (s-phase fraction and epidermal growth factor receptor) can predict relapse and survival in patients with node-negative primary breast cancer - Kaufmann, Manfred; Minckwitz, Gunter von; Finn, H. P.; Schmid, Hans; Goerttler, Klaus; Bastert, Gunther (Onkologie, 1994)
Background: In most cases of node-negative breast cancer, clinical outcome is relatively good after surgical treatment. It is necessary, however, to determine prognostic factors for the identification of high- and low-risk subgroups concerning recurrence and death, because only patients with excellent prognosis require no further treatment. The objective of the study was to select a few potential factors for a prognostic index that can be used in clinical practice. Patients and Methods: In 108 patients with primary node-negative breast cancer we examined simultaneously the impact of new prognosticators on disease-free survival (DFS) and overall survival (OAS): DNA ploidy, S-phase fraction (SPF), cycling index encoded by Ki 67, estrogen and progesterone receptor status, epidermal growth factor receptor (EGF-R), Her 2b/neu oncoprotein, and GP170 glycoprotein. Only fresh-frozen tissue was used. Median time of follow-up was 42 months. Results: By means of the log-rank analysis we found that patients with a SPF > 5% of the tumor had a significantly shorter DFS (p = 0.01) and OAS (p = 0.01) than patients with a SPF < 5%. Similar results for OAS were obtained for tumors with EGF-R levels > 15 fmol/mg versus < 15 fmol/mg (p = 0.05) and tumors of grade III versus grade I/II (p = 0.03). A low progesterone receptor level ( < 20 fmol/mg) indicated a short DFS (p = 0.06) but was of no prognostic value for OAS. Using a combination of SPF and EGF-R, a group of patients with extremely good prognosis (no patients have died) could be identified, if at least one factor was favorably expressed. If both factors were elevated clinical outcome was poor (DFS: p = 0.003; OAS: p = 0.002). By including histological grading in the analysis, a prognostic index could be described when discriminated patients with good, medium, and high risk for relapse and survival (DFS: p = 0.009; OAS: p = 0.001). Conclusions: Out of 11 parameters, grading, SPF, and EGF-R have been selected for a prognostic index. This prognostic index can be used to classify patients with node-negative primary tumors in different risk categories, so that an individual and risk-adapted adjuvant systemic therapy becomes possible, according to the treatment recommendations outside clinical trials.
Elektronische Reproduktion der Druck-Ausgabe 11. Mai 2009
Gesehen am 14.02.2024